Visceral and ectopic fat, atherosclerosis, and cardiometabolic disease: a position statement. Issue 9 (September 2019) - Neeland, Ian J; Ross, Robert; Després, Jean-Pierre; Matsuzawa, Yuji; Yamashita, Shizuya; Shai, Iris; Seidell, Jaap; Magni, Paolo; Santos, Raul D; Arsenault, Benoit; Cuevas, Ada; Hu, Frank B; et al.
Summary: Findings from epidemiological studies over the past 30 years have shown that visceral adipose tissue, accurately measured by CT or MRI, is an independent risk marker of cardiovascular and metabolic morbidity and mortality. Emerging evidence also suggests that ectopic fat deposition, including hepatic and epicardial fat, might contribute to increased atherosclerosis and cardiometabolic risk. This joint position statement from the International Atherosclerosis Society and the International Chair on Cardiometabolic Risk Working Group on Visceral Obesity summarises the evidence for visceral adiposity and ectopic fat as emerging risk factors for type 2 diabetes, atherosclerosis, and cardiovascular disease, with a focus on practical recommendations for health professionals and future directions for research and clinical practice. We discuss the measurement of visceral and ectopic fat, pathophysiology and contribution to adverse health outcomes, response to treatment, and lessons from a public health programme targeting visceral and ectopic fat. We identify knowledge gaps and note the need to develop simple, clinically applicable tools to be able to monitor changes in visceral and ectopic fat over time. Finally, we recognise the need for public health messaging to focus on visceral and ectopic fat in addition to excess bodyweight to better combat the growing epidemic of obesity worldwide.